Implementation of a prototype of a dispenser of chocolates - Velásquez Costa, José Antonio (2009)
This article describes the implementation for a prototype of a chocolate filling and dispensing, using automation techniques for automatic control of the process. The design of the prototype was performed in a software CAD (computer aided design) and for the implementation was required pneumatic devices, sensors, programmable logic controller (PLC). All these components are integrated into a conveyor belt.